I poli della poesia e il respiro del verso. Glosse a Platone, Dante, Celan, Zanzotto - Desideri, Fabrizio (Bollettino Filosofico, 2017)
The limit between poetical and philosophical speech has always been as clear as labile. Conjoining these two characteristics, it could be said that this limit is close to a paradox. The way a speech presents itself will never include the criteria of its traceability. The essay moves among Plato, Dante, Celan and Zanzotto.